Graves’ Disease Mechanisms: The Role of Stimulating, Blocking, and Cleavage Region TSH Receptor Antibodies - Morshed, S. A.; Davies, T. F. (Hormone and Metabolic Research, 2015)
The immunologic processes involved in Graves’ disease (GD) have one unique characteristic – the autoantibodies to the TSH receptor (TSHR) – which have both linear and conformational epitopes. Three types of TSHR antibodies (stimulating, blocking, and cleavage) with different functional capabilities have been described in GD patients, which induce different signaling effects varying from thyroid cell proliferation to thyroid cell death. The establishment of animal models of GD by TSHR antibody transfer or by immunization with TSHR antigen has confirmed its pathogenic role and, therefore, GD is the result of a breakdown in TSHR tolerance. Here we review some of the characteristics of TSHR antibodies with a special emphasis on new developments in our understanding of what were previously called “neutral” antibodies and which we now characterize as autoantibodies to the “cleavage” region of the TSHR ectodomain.
Keywords: Graves’ disease; thyroid; TSH-receptor antibodies; TSH; signaling